Facilities managers awareness with the symptom of sick building syndrome in office building / Muhammad Hafiez Shafiq Arifin Loh - Shafiq Arifin Loh, Muhammad Hafiez (2014)
Sick building syndrome is a form of sickness that gives effect towards building occupants, which normally occur at the office building. Furthermore In office building there are also contaminated air that will make the building occupant felt uncomfortable and also will cause sickness to themselves, in Malaysia office building majority of the building are more contaminated in term of mechanical ventilation. The aim of the study is to establish the level of awareness among facilities managers towards sick building syndrome in office building. Therefore, to accomplish the aim three (3) objectives have been outlined which is to study the effect of sick building syndrome towards building occupant, to identify the sick building syndrome causes through maintenance in office building and finally to examine the perception from facilities managers towards sick building syndrome. The sample of this study was recruited from three (3) selected case studies which are the private office building Kuala Lumpur and also Shah Alam, and the data have been gather a qualitative and quantitative data collection methods. Fora qualitative method, this study used a semi structured interview which focuses on the facilities managers while for a qualitative data a set of questionnaire have been distributed to 60 respondents of building occupants from three (3) case studies. The interview result were analyzed using content analysis, while the Statistical Package for Social Science (SPSS) was used to analyses data collected from questionnaire survey. Based on the study the result have been gather there are cases of sick building syndrome in an office building among building occupant and the level of knowledge also awareness of the facilities.